Novel Map Biopsy Technique to Define the Extent of Infection Before Penetrating Keratoplasty for Acanthamoeba Keratitis. Issue 3 (30th March 2023) - Simpson, Alasdair; Sarode, Deep; Lockington, David; Ramaesh, Kanna
Abstract : Purpose: The purpose of this study was to report a novel approach of prepenetrating keratoplasty (PKP) corneal map biopsies to define the extent of Acanthamoeba cyst infiltration in recalcitrant Acanthamoeba keratitis. Methods: Corneal map biopsies were performed 1 week before PKP. Four biopsies, 1 from each peripheral corneal quadrant, were obtained to delineate the extent of microscopic infection. Histological results of these map biopsies were used to determine the size and location of the subsequent PKP. Results: In our first case, map biopsies revealed Acanthamoeba cysts in 2 of the 4 biopsies. This led to an inferotemporally eccentric 8.5-mm PKP. The final histology report indicated that the closest resection margin was 0.08 mm. In our second case, the peripheral map biopsies were clear and an inferiorly eccentric 8.25-mm PKP was performed. The final histology report indicated that the closest resection margin was 2.3 mm. Both grafts have remained clear at 6 months postoperatively. Conclusions: Map biopsies of the cornea can achieve total removal of the corneal tissues infested with Acanthamoeba cysts and prevent reinfection of the donor graft.